Effect of the administration of quebracho extract on rumen fermentacion and diet digestibility in sheep - Hervas, G.=700 1 Frutos, P.; Mantecon, A.R.; Giraldez, F.J.
(Es, En)
ilus., 18 ref.
Keywords: DEGRADACION; RUMEN; DIGESTIBILIDAD; TANINOS; OVEJA; ESPAÑA; TANINOS CONDENSADOS